Transoral Laser-Assisted Total Laryngectomy: Expanding the TLM’s World - Ahmadi, Aslan; Mohebbi, Saleh; Kazemi, Masoud; Sanaei, Ayda (Case Reports in Otolaryngology, 2020)
Introduction. The introduction of laryngeal transoral procedures has created a shift in the treatment of laryngeal cancers towards the primary surgical management of patients. In this study, we aimed to evaluate the safety, efficacy, and feasibility of the transoral laser-assisted total laryngectomy (TLM-TL) in advanced laryngeal cancer. Case presentation. In this case report, we describe a case of a 50-year-old male patient presented to the otorhinolaryngology clinic with a history of hoarseness and odynophagia since 6 months. Based on the pathological and imaging findings, the diagnosis of stage IVa laryngeal squamous cell carcinoma with the involvement of the base, tongue, and left palatine tonsil was made for the patient, and transoral total laryngectomy with partial glossectomy via the TLM technique was planned. Result. The tumor was successfully resected by TLM-TL with clear surgical margins. No complication was observed after the surgery. Good functional recovery was obtained regarding swallowing and speech. The patient’s oncologic and functional outcomes were evaluated for 2 years. Everything was satisfactory with good long-term cosmetic and laryngopharyngeal functional outcome and no sign of tumor recurrence. Conclusions. TLM-TL is a minimally invasive and cost-benefit endoscopic surgical procedure feasible in advanced laryngeal cancer with good long-term oncological and functional outcome. It could limit postoperative complications, mainly the incidence of pharyngocutaneous fistulae. It is also associated with better satisfaction after TL due to cosmetic benefits.